Investigation on cellulolytic and proteolytic activities of the endophytic fungi isolated from medicinal plants - Tan, Eng Hong (2015)
Endophytic fungi are the fungi that reside in t he p lant internal tissues. They are an e xcellent source of bioactive natural compounds such as antimicrobial, antiviral and anticancer compounds. They are also an alternative source other than the commercial bacteria to produce extracellular enzymes to meet th e high industrial demand. Scientists found out that there are more than a million of fungal species still yet to be identified. Novel fungal species are believed to be discovered among the under explored endophytic fungi. This study was to isolate and ide ntify endophytic fungi from 10 medicinal plants, screen fungal isolates for their cellulolytic and proteolytic abilities and determine the cellulase and protease activities usi ng spectrophotometric methods. From the study, fungal isolates IS02, IS03, IS05, IS07 and IS10 showed positive results in cellulolytic screening while IS06, IS08, IS09 and IS10 showed positive res ults in proteolytic screening. Cellulase producers IS07 and IS03 ) and protease producers (IS06 and which recorded the highest and sec ond highest Index of Rela tive Enzyme Activity were subjected to spectrophotometric assays. IS03 and IS07 showed their highest cellulase activities on day 10 which were 0.0055 U/mL and 0.0093 U/mL respectively. IS06 and IS09 showed their highest protease ac tivities on day 10 which were 0.0263 U/mL and 0.0212 U/mL respectively. IS06 was suspected to be Penicillium sp. whereas IS07 was suspected to be Aspergillus sp. Non spore formers IS03 and IS09 were failed to identify using microscopic method.